Molecular mechanism of flavin photoprotection by archaeal dodecin: photoinduced electron transfer and Mg2+-promoted proton transfer - Scheurer, Maximilian; Brisker-Klaiman, Daria; Dreuw, Andreas (The journal of physical chemistry. B, Biophysics, biomaterials, liquids, and soft matter, 2017)
Photoinduced biochemical reactions are ubiquitously governed by derivatives of flavin, which is a key player in a manifold of cellular redox reactions. The photoreactivity of flavins is also one of their greatest disadvantages as the molecules are sensitive to photodegradation. To prevent this unfavorable reaction, UV-light-exposed archaea bacteria, such as Halobacterium salinarum, manage the task of protecting flavin derivatives by dodecin, a protein which stores flavins and efficiently photoprotects them. In this study, we shed light on the photoprotection mechanism, i.e., the excited state quenching mechanism by dodecin using computational methodology. Molecular dynamics (MD) simulations unraveled the hydrogen bond network in the flavin binding pocket as a starting point for proton transfer upon preceding electron transfer. Using high-level ab initio quantum chemical methods, different proton transfer channels have been investigated and an energetically feasible Mg2+-promoted channel has been identified fully explaining previous experimental observations. This is the first extensive theoretical study of archaeal dodecin, furthering the understanding of its photocycle and manipulation.